2014
DOI: 10.1016/j.marenvres.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modulates the response of the thermophilous sea urchin Arbacia lixula early life stages to CO2-driven acidification

Abstract: a b s t r a c tThe increasing abundances of the thermophilous black sea urchin Arbacia lixula in the Mediterranean Sea are attributed to the Western Mediterranean warming. However, few data are available on the potential impact of this warming on A. lixula in combination with other global stressors such as ocean acidification. The aim of this study is to investigate the interactive effects of increased temperature and of decreased pH on fertilization and early development of A. lixula. This was tested using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…Previous combined stressor studies, on other intertidal sea urchin species, have also reported no effect on larval survival (Wolfe et al, 2013;Gianguzza et al, 2014). Table 3 Physico-chemical seawater parameters for each experimental treatment tested for postlarvae of Paracentrotus lividus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous combined stressor studies, on other intertidal sea urchin species, have also reported no effect on larval survival (Wolfe et al, 2013;Gianguzza et al, 2014). Table 3 Physico-chemical seawater parameters for each experimental treatment tested for postlarvae of Paracentrotus lividus.…”
Section: Discussionmentioning
confidence: 94%
“…Species that live in habitats subject naturally to high levels of environmental variability (wide natural range), may have more resilience to warming and/or acidification of sea water, compared to those living in more stable habitats (narrow natural range) (Melzner et al, 2009;Gobler, 2009, 2011;Matson et al, 2012;Wolfe et al, 2013). Species exposed to highly variable environmental conditions, for example intertidal species, could therefore show greater robustness to future climate change scenarios, than those living in more constant environments (Sheppard-Brennand et al, 2010;Martin et al, 2011;Moulin et al, 2011;Foo et al, 2012;Byrne et al, 2013a;Gianguzza et al, 2014; but see Byrne et al, 2013b for review). Therefore, it seems likely that climate change will favor species with wide thermal windows, short generation times, and a diverse range of genotypes in their populations (P€ ortner and Farrell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Energetic limitation, such as under inadequate food supply, can have a substantial effect upon responses to OA; positive, neutral and negative metabolic responses can all be observed with similar magnitude changes in pH when under energylimiting conditions (Gianguzza et al, 2014). This highlights the need for more holistic models of species energetics under combined stressors, incorporating factors such as energy available for growth, responses under energetic limitation, whether the baseline metabolism is close to optimal, and attainment of physiological equilibrium through adequate acclimation (Gianguzza et al, 2014;Pan et al, 2015). We saw very limited ability to increase resource consumption even with an increase of metabolic rate of 44%.…”
Section: Effects Of Ocean Acidification On Sea Urchin Metabolismmentioning
confidence: 99%
“…Copper plays an important role in metabolism, as it is a cofactor for numerous enzymes involved with redox reactions. Because Cu is an essential nutritional element, its lack may lead to neural aberrations during embryonic development (Turski and Thiele, 2009), but evidences of its toxicity at high concentrations were also reported (Gomes et al, 2011;Perreault et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A. lixula, together with the edible sea urchin Paracentrotus lividus, are the most abundant echinoids in the Mediterranean. They play an important ecologic role in the littoral ecosystem, where they control the algal communities growth (Gianguzza et al, 2014;Gianguzza and Bonaviri, 2013;Martin et al, 2011;Poleza et al, 2014;Wangensteen et al, 2013). Also, it was demonstrated that A. lixula and P. lividus show similar sensitivities to chemicals (Carballeira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%